Characterization and antioxidant activity of wheat bran polysaccharides modified by Saccharomyces cerevisiae and Bacillus subtilis fermentation. (January 2021) - Chen, Qiuyan; Wang, Ruifang; Wang, Yuan; An, Xiaoping; Liu, Na; Song, Min; Yang, Yanping; Yin, Na; Qi, Jingwei
Abstract: Fermentation is considered as one of the most useful biological modification techniques to increase the bioactivity of polysaccharides. In this study, Saccharomyces cerevisiae and Bacillus subtilis were used to ferment wheat bran, and the effects of the fermentation on the structural characteristics and antioxidant activity of wheat bran polysaccharides were investigated. Two polysaccharides were isolated from unfermented and fermented wheat bran and labelled as wheat bran polysaccharides-1 (WBP-1) and fermented wheat bran polysaccharides-1 (FWBP-1), respectively. The results showed fermentation increased the content of total polysaccharides, enhanced the proportions of rhamnose, xylose and arabinose and improved the proportion of fucose to a detectable level. After fermentation, the molecular weight of FWBP-1 (21.19 kDa) was lower than that of WBP-1 (52.02 kDa). In vitro, FWBP-1 exhibited higher reducing power and stronger 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical and hydroxyl radical scavenging activities. In zebrafish model, FWBP-1 also displayed superior protective effects against 2, 2′-azobis(2-methylpropionamidine) dihydrochloride (AAPH)-induced reactive oxygen species (ROS) production, lipid peroxidation, and cell death. Taken together, S. cerevisiae and B. subtilis fermentation could change the structural characteristics and enhance the antioxidant activity of polysaccharides from wheat bran. Graphical abstract: Image 1 Highlights: Saccharomyces cerevisiae and Bacillus subtilis were used to ferment wheat bran (WB). Fermentation altered the structural characteristics of WB polysaccharides. In vitro, fermented-polysaccharides displayed higher reducing power and free radical scavenging activities. In zebrafish model, fermented-polysaccharides exhibited superior protective effects against AAPH-induced oxidative stress.